Pengaruh Elemen E-Commerce terhadap Kinerja Usaha Mikro Kecil dan Menengah di Kota Bandar Lampung - Nawawi, Arvira Meita; Sudrajat; Desriani, Neny (Regress: Journal of Economics & Management, 2023)
The purpose of this study is to empirically test the influence of E-Commerce Elements, namely Organizational Support, Technological Competence and External Environment on the Performance of Micro, Small and Medium Enterprises in Bandar Lampung City. This research uses a purposive sampling technique in taking samples. Based on predetermined criteria, 52 Culinary MSMEs were obtained located around the Lampung University campus. The type of data used was primary data obtained from distributing questionnaires. The analytical method used is multiple linear regression analysis. The research results show that organizational support influences MSME performance. Technological Competency has a positive and significant effect on MSME Performance. The external environment has a positive and significant effect on MSME performance.